Is what we understand and imagine what we look for? The teachers’ conceptualisation of textual coherence and its implications for classroom writing assessment - Truck-Biljan, Ninočka; Molnar, Draženka (ExELL, 2025)
For over four decades, coherence has intrigued researchers in text linguistics and applied linguistics, particularly in texts written by non-native speakers. However, insights into teachers’ understanding of this concept remain underexplored. This study aimed to identify foreign language teachers’ metaphorical conceptualisations of textual coherence and explore the implications for classroom writing assessment, based on the evaluation of essays written in Croatian, English, German, French, and Hungarian as modern foreign languages at the upper secondary and higher education levels. The participants included 17 secondary school teachers and 26 university lecturers. A mixed-method approach was used in this study. The findings showed that teachers’ views on coherence were shaped by their professional knowledge, experience, and assessment practices. Metaphors and the writing assessment seemed to be mirroring each other, highlighting the importance of feedback on conceptualisations of coherence and raising awareness of types of coherence among teachers. The use of precisely predetermined and agreed descriptors could result in achieving greater objectivity during classroom assessment in the long run.